GAMBARAN PERILAKU PEMELIHARAAN KESEHATAN GIGI DAN MULUT BERDASARKAN JENIS KELAMIN PADA SISWA MTS NURUL HUDA CIMANGGU KABUPATEN MAJALENGKA (Jurnal Terapi Gigi dan Mulut, 2023)
Behavior is the action or activity of the activity of a living being. Dental health behavior consists of a person's knowledge, attitudes and actions to achieve an optimal degree of dental health. Maintaining healthy teeth and mouth is to keep teeth and mouth in a healthy state which is free from pain and various oral diseases. Dental and oral health is very important because it has many functions such as mastication, speech, and appearance. The purpose of this paper is to find out a picture of dental and oral health maintenance behaviors based on gender in mts Nurul Huda Cimanggu students of Majalengka Regency with a total of 72 respondents. This type of research is descriptive with an approach in the form of a survey. The research data collection technique is by observation and interview methods. Analysis of the data used by means of univariate analysis of each variable. The results of this study were perilaku based on the level of knowledge of maintaining good dental and oral health in the category of 14 respondents (19.4%), 49 (68.1%) moderate behavior, 9 (12.5%) bad behavior. Based on sikap 11 respondents were good (15.3%), 44 (61.1%) were moderate attitudes, 17 (23.6%) were bad attitudes. Based on the act of brushing your teeth, 14 respondents had good actions (19.4%), and 58 respondents had bad actions (80.6%). The conclusion of this study is that the male sex has an average value of dental and oral health maintenance behaviors by 41.7% lower than the female sex by 58.3%.